Clinical significance of presence of accessory foramen transversarium in typical cervical vertebrae - N., Esakkiammal; Chauhan, Renu (International Journal of Research in Medical Sciences, 2016)
Background: The cervical vertebrae are smallest of all the vertebrae present in the vertebral column. It is characterized by a foramen in each transverse process. The foramen transversarium (FT) of 6th to 1st cervical vertebrae transmits vertebral vessels and sympathetic nerves. Presence of another foramen apart from FT in the transverse process of cervical vertebrae is called accessory FT. Anatomical knowledge of these variations are helpful for conducting cervical spinal surgeries by the surgeons in order to prevent injury to vertebral vessels and sympathetic nerves. Methods: The present study was conducted in the department of anatomy, UCMS and GTB Hospital, Delhi, India. A total number of 241 dried cervical vertebrae were collected from the bone bank of the Department of Anatomy. Presence of any variation from the normal anatomy of the cervical vertebrae were noted and photographed. Results: Out of 241 cervical vertebrae (typical and atypical), the accessory FT was noted in typical cervical vertebrae only. Accessory FT was seen in 37 (27.6%) vertebrae, out of 134 typical cervical vertebrae. These accessory FT were either bilateral complete in 4 (2.9%) or incomplete 9 (6.7%) or unilateral complete 6 (4.5%) and unilateral incomplete 12 (8.9%) were observed. Six (4.5%) typical cervical vertebrae showed presence of complete accessory FT on one side and incomplete accessory FT on the other side in the same vertebra. Conclusions: Knowledge of variations of the presence of accessory FT in the typical cervical vertebrae is not only important to anatomist but also to radiologist in identifying the presence of duplicate vertebral artery and hence helping the neuro surgeons in preventing accidental bleeding from the vertebral artery while performing surgery on the cervical spine.